Pleural schistosomiasis masquerading as tubercular pyopneumothorax: World's first case report - Vadala, Rohit (Lung India, 2021)
Schistosomiasis is an uncommon waterborne helminthic infection that infects humans. Although it is not prevalent in India, many cases are reported due to contact with infested water bodies. Schistosomiasis primarily involves the lower urinary tract and colorectal region. Pulmonary schistosomiasis, although very unusual, has been described with the systemic manifestation of the disease; however, pleural involvement with schistosomiasis has never been described before in the literature. We report this first case of pleural schistosomiasis masquerading as tuberculosis, which posed a diagnostic challenge and later a new learning point in the presentation of the disease.